Attitudes toward Palliative Care and the Influence of the Service Marketing Mix on the Intention to Use Palliative Care Services in Hospitals Southern Thailand - Tongnuanoun, Thanittee; Tantasuntisakul , Warangkana (Journal of Research in Nursing-Midwifery and Health Sciences, 2025)
Objectives: This study attitudes toward palliative care and the service marketing mix that influence the intention to use palliative care services in hospitals in Southern Thailand. Methods: The sample population includes families of terminally ill patients, terminally ill patients themselves, and individuals with critical illness experiences who possess an understanding of palliative care and have previously used palliative care services in hospitals in southern Thailand. A total of 400 participants were surveyed. Data were collected using questionnaires and analyzed through descriptive and inferential statistics, specifically using multiple regression analysis to determine factors impacting the intention to use palliative care services. Results: The study found that attitudes and service marketing mix specifically the physical evidence and promotion components significantly influence the intention to use palliative care services in hospitals Southern Thailand. Conclusion: The study’s findings provide a foundational basis for enhancing palliative care systems and can be applied to promote health within Thailand’s healthcare system, particularly in hospitals in southern Thailand.